2020
DOI: 10.18203/2319-2003.ijbcp20202947
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hematological parameters in oral cancer and oral pre-cancer

Abstract: Background: Oral squamous cell carcinoma (OSCC) is the most common public health issue in Indian population. Quite a large number of OSCC cases are preceded by potentially malignant disorders of oral cavity. The need for simple diagnostic marker for early diagnosis and thus better therapeutic outcome is imperative. The current study aims to evaluate hematological parameters such as hemoglobin, bleeding time, clotting time, total leucocyte count (TLC) and differential leucocyte count (DLC) in OSCC and oral pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Many study results have shown that high PLR and NLR are risk factors for the prognosis of oral cancer (Chen et al, 2016; Jariod‐Ferrer et al, 2019; Kawakita et al, 2017; Mascarella et al, 2018; Ong et al, 2017; Park et al, 2017; Sano et al, 2018; Singh et al, 2021; Tangthongkum et al, 2017; Tazeen et al, 2020; Yu et al, 2019). Two studies have suggested that at this point, PLR is 135 (Chen et al, 2016; Tangthongkum et al, 2017) and NLR is 2.2 (Hasegawa et al, 2020), and so, this study divided the patients into preoperative PLR ≤135 group and <135 group according to preoperative PLR, and preoperative NLR ≤2.2 group and >2.2 group according to preoperative NLR for analyzing the differential effects on the survival of patients with oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many study results have shown that high PLR and NLR are risk factors for the prognosis of oral cancer (Chen et al, 2016; Jariod‐Ferrer et al, 2019; Kawakita et al, 2017; Mascarella et al, 2018; Ong et al, 2017; Park et al, 2017; Sano et al, 2018; Singh et al, 2021; Tangthongkum et al, 2017; Tazeen et al, 2020; Yu et al, 2019). Two studies have suggested that at this point, PLR is 135 (Chen et al, 2016; Tangthongkum et al, 2017) and NLR is 2.2 (Hasegawa et al, 2020), and so, this study divided the patients into preoperative PLR ≤135 group and <135 group according to preoperative PLR, and preoperative NLR ≤2.2 group and >2.2 group according to preoperative NLR for analyzing the differential effects on the survival of patients with oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many study results have shown that high PLR and NLR are risk factors for the prognosis of oral cancer (Chen et al, 2016;Jariod-Ferrer et al, 2019;Kawakita et al, 2017;Mascarella et al, 2018;Ong et al, 2017;Park et al, 2017;Sano et al, 2018;Singh et al, 2021;Tangthongkum et al, 2017;Tazeen et al, 2020;Yu et al, 2019).…”
Section: Ta B L Ementioning
confidence: 99%